Frequency and susceptibility to penicillin and methicillin of Staphylococcus aureus environmental isolations at a Cuenca´s hospital - Carlos Andrade T; Paola Orellana B (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Staphylococcus aureus is a pathogen associated with intrahospital infections commonly found in the nasal cavities and the hands of health personnel, as well as, on environmental surfaces; which become potential reservoirs and transmission vehicles of infections. In this study the frequency and susceptibility to penicillin and methicillin of environmental isolates of S. aureus in a hospital to Cuenca were analyzed. 50 samples (30 of two operating room and 20 of the intensive care room) were collected. S. aureus was identified by phenotypic tests and molecular detection of the nuc gene. The susceptibility to methicillin and penicillin was determined by agar disc diffusion method and the blaZ and mecA genes by polymerase chain reaction. The frequency of S. aureus was 6% (3/50 strains). Resistance to penicillin and methicillin was 66.6% (2/3 strains). The blaZ and mecA genes were detected in the two strains resistant to penicillin and methicillin. The low frequency of S. aureus may be related to the environments analyzed; because the surfaces sampled are areas where emphasis is placed on the application of hygiene and disinfection protocols for ensure adequate decontamination.